Reaction of Nitrilimines with Keto-Alkoxycarbonyl-Hydrazones: Synthesis of Substituted 1,2,4-Triazoles and Heterocyclic Spiro Compounds - M. Awad, Boshra; S. Ferwanah, Abdel-Rahman; M. Awadallah, Adel; M. EL-Halabi, Nabil (Asian Journal of Chemistry, 2010)
Hydrazonoyl halides (1) react with alkanone and cycloalkanone alkoxycarbonylhydrazones (3) to give the cycloaddition products 4,5-dihydro-1,2,4-triazoles (7a–h) rather than the tetrazine cyclocondensation products. Reaction of (7c,d) with hydoxylamine gave the corresponding oximes (8c,d) of these heterocycles.